Endovascular treatment versus no endovascular treatment after 6–24 h in patients with ischaemic stroke and collateral flow on CT angiography (MR CLEAN-LATE) in the Netherlands: a multicentre, open-label, blinded-endpoint, randomised, controlled, phase 3 trial. Issue 10385 (22nd April 2023) - Olthuis, Susanne G H; Pirson, F Anne V; Pinckaers, Florentina M E; Hinsenveld, Wouter H; Nieboer, Daan; Ceulemans, Angelique; Knapen, Robrecht R M M; Robbe, M M Quirien; Berkhemer, Olvert A; van Walderveen, Marianne A A; Lycklama à Nijeholt, Geert J; Uyttenboogaart, Maarten; et al.
Summary: Background: Endovascular treatment for anterior circulation ischaemic stroke is effective and safe within a 6 h window. MR CLEAN-LATE aimed to assess efficacy and safety of endovascular treatment for patients treated in the late window (6–24 h from symptom onset or last seen well) selected on the basis of the presence of collateral flow on CT angiography (CTA). Methods: MR CLEAN-LATE was a multicentre, open-label, blinded-endpoint, randomised, controlled, phase 3 trial done in 18 stroke intervention centres in the Netherlands. Patients aged 18 years or older with ischaemic stroke, presenting in the late window with an anterior circulation large-vessel occlusion and collateral flow on CTA, and a neurological deficit score of at least 2 on the National Institutes of Health Stroke Scale were included. Patients who were eligible for late-window endovascular treatment were treated according to national guidelines (based on clinical and perfusion imaging criteria derived from the DAWN and DEFUSE-3 trials) and excluded from MR CLEAN-LATE enrolment. Patients were randomly assigned (1:1) to receive endovascular treatment or no endovascular treatment (control), in addition to best medical treatment. Randomisation was web based, with block sizes ranging from eight to 20, and stratified by centre. The primary outcome was the modified Rankin Scale (mRS) score at 90 days after randomisation. Safety outcomes included all-cause mortality at 90 days after randomisation and symptomatic intracranial haemorrhage. All randomly assigned patients who provided deferred consent or died before consent could be obtained comprised the modified intention-to-treat population, in which the primary and safety outcomes were assessed. Analyses were adjusted for predefined confounders. Treatment effect was estimated with ordinal logistic regression and reported as an adjusted common odds ratio (OR) with a 95% CI. This trial was registered with the ISRCTN, ISRCTN19922220. Findings: Between Feb 2, 2018, and Jan 27, 2022, 535 patients were randomly assigned, and 502 (94%) patients provided deferred consent or died before consent was obtained (255 in the endovascular treatment group and 247 in the control group; 261 [52%] females). The median mRS score at 90 days was lower in the endovascular treatment group than in the control group (3 [IQR 2–5] vs 4 [2–6]), and we observed a shift towards better outcomes on the mRS for the endovascular treatment group (adjusted common OR 1·67 [95% CI 1·20–2·32]). All-cause mortality did not differ significantly between groups (62 [24%] of 255 patients vs 74 [30%] of 247 patients; adjusted OR 0·72 [95% CI 0·44–1·18]). Symptomatic intracranial haemorrhage occurred more often in the endovascular treatment group than in the control group (17 [7%] vs four [2%]; adjusted OR 4·59 [95% CI 1·49–14·10]). Interpretation: In this study, endovascular treatment was efficacious and safe for patients with ischaemic stroke caused by an anterior circulation large-vessel occlusion who presented 6–24 h from onset or last seen well, and who were selected on the basis of the presence of collateral flow on CTA. Selection of patients for endovascular treatment in the late window could be primarily based on the presence of collateral flow. Funding: Collaboration for New Treatments of Acute Stroke consortium, Dutch Heart Foundation, Stryker, Medtronic, Cerenovus, Top Sector Life Sciences & Health, and the Netherlands Brain Foundation.